IMPLEMENTASI SUSTAINABLE DEVELOPMENT GOALS (SDGs) DAN STRATEGI PENGELOLAAN SUMBER DAYA MANUSIA DI PT KANISIUS YOGYAKARTA (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study focuses on seeing whether there is an influence of the implementation or application of government programs, namely the Sustainable Development Goals (SDGs) by focusing on the eighth goal, namely about decent work for the community and the continuity of a business, and also to see the influence of human resource management strategies on employee performance at PT Kanisius Printing Publisher located in Yogyakarta either partially or simultaneously. The author in conducting the study used a descriptive quantitative method by giving questionnaires to respondents who were structural officials at PT Kanisius. From the results of the research that has been done, it shows that there is a positive influence of the two variables on employee performance, however, the SDGs implementation variable does not directly have a significant effect on employee performance. So if referring to the results of this study, PT Kanisius can focus more on improving HR management strategies to maximize employee performance.
Keywords: SDG 8 Implementation; HR Strategy; Employee Performance